Reestructuración técnico administrativa de la empresa Servicio Técnico Martínez en el municipio de Chía Cundinamarca (2019)
The present degree project develops the technical-administrative restructuration of the company Technical Service Martinez, since, this have been presenting faults in the different processes that are carried out to achieve the appropriate response to the client. The purpose of this project is to provide the company with different proposals for improvement in its processes, achieving a reduction in the response time of the promise to the client.